(untitled) (Advancements in Homeopathic Research, 2023)
Hypertension, the persistent increase in the blood pressure (BP) above the normal values, is a very worrying public health problem. It causes high morbidity and mortality globally. Pre-hypertension is also a sub-clinical condition, but remains a public health challenge. It is a major risk factor for subsequent cardiovascular diseases. Although defining hypertension is very difficult, but individual patient risk only assess from severity of hypertension. Appropriate intervention is needed to stop its progression and other cardiovascular diseases. The use of homeopathic remedies is rising in the modern time especially in chronic diseases like hypertension and is proved effective in various clinical practices. In this clinical experiment, we have tried to conclude that there might be significant improvement among one group of patients suffering from different symptoms due to pre-hypertension & hypertension by administering combination homeopathic medicine, Hypervis & there was negligible or no improvement while using placebo doses on another group of patients in over 3 months of intervention while both the groups received standardized recommendations for dietary and lifestyle modifications.